Clomipramine potentially induced fatal torsades de pointes in a patient with acute decompensated heart failure: a case report - Rong-Hua Wang; Yu-Liang Lu; Jia-Hui Lu (Frontiers in Psychiatry, 2025)
BackgroundWhile clomipramine is generally considered lower risk for QT prolongation among tricyclic antidepressants, its potential to induce torsades de pointes (TdP) remains poorly characterized, particularly in patients with multiple risk factors.Case presentationA 78-year-old male with a history of hypertension, atrial fibrillation, and post-stroke depression presented to the emergency department with a one-week history of chest distress. Initial evaluation revealed atrial fibrillation with a prolonged QTc interval of 550 ms on electrocardiogram (ECG) monitoring, and elevated B-type natriuretic peptide (1130 pg/mL). The patient was admitted for acute decompensated heart failure and treated with torasemide intravenously while continuing clomipramine (25 mg daily) for depression. Within 24 hours, he experienced multiple episodes of torsades de pointes (TdP), coinciding with hypokalemia (serum potassium: 3.21 mmol/L). Despite corrective measures, including potassium and magnesium supplementation, the patient developed ventricular fibrillation and cardiac arrest, leading to death.ConclusionThis case highlights the potential risk of clomipramine-induced QT prolongation and TdP, particularly in patients with acute heart failure and electrolyte imbalances, underscoring the need for careful risk assessment and monitoring in such populations.